2007
DOI: 10.4269/ajtmh.2007.76.1033
|View full text |Cite
|
Sign up to set email alerts
|

Higher Production of Peripheral Blood Macrophage Migration Inhibitory Factor in Healthy Children With a History of Mild Malaria Relative to Children With a History of Severe Malaria

Abstract: Plasmodium falciparum malaria is one of the leading causes of childhood morbidity and mortality in sub-Saharan Africa. The host immune response to P. falciparum is a critical determinant of malarial pathogenesis and disease outcomes. Macrophage migration inhibitory factor (MIF) is a central regulator of innate immune responses to bacterial and parasitic infections. Our recent investigations demonstrated that peripheral blood MIF production was suppressed in children with severe malaria. Because examination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…At the moment, there are opposing views. Some reports indicated a pathogenic role for mMIF during P. falciparum malaria (35,43), while others showed that higher levels of mMIF production correlate with protection from severe disease (3)(4)(5)(6). The presence of pMIF in the sera of P. falciparum malaria patients has been reported but has not been factored into this analysis (51).…”
Section: Vol 78 2010 P Yoelii Mif Alters the Course Of Blood-stagementioning
confidence: 99%
See 1 more Smart Citation
“…At the moment, there are opposing views. Some reports indicated a pathogenic role for mMIF during P. falciparum malaria (35,43), while others showed that higher levels of mMIF production correlate with protection from severe disease (3)(4)(5)(6). The presence of pMIF in the sera of P. falciparum malaria patients has been reported but has not been factored into this analysis (51).…”
Section: Vol 78 2010 P Yoelii Mif Alters the Course Of Blood-stagementioning
confidence: 99%
“…It is important to point out, however, that several studies of uncomplicated and severe P. falciparum malaria assign a protective role for mMIF. In some cases, high circulating levels of mMIF were associated with reduced anemia and with milder episodes of malaria in children (3,4,6). An explanation for the apparent discrepancies is not obvious.…”
mentioning
confidence: 99%
“…These studies have shown an inverse correlation between MIF concentrations and parasite burden [68] and suggested a protective role for MIF during noncomplicated malaria [67] and human SMA [46]. Furthermore, the data above is corroborated by an experimental work with healthy European volunteers showing that MIF concentrations are decreased in response to early P. falciparum infection but are increased in response to antimalarial treatment [45].…”
Section: Host Mif Seems To Be Protective In Human Malariamentioning
confidence: 88%
“…Studies conducted in Africa have reported lower concentrations of MIF in P. falciparum -infected children when compared to asymptomatic ones [46, 67, 68]. These studies have shown an inverse correlation between MIF concentrations and parasite burden [68] and suggested a protective role for MIF during noncomplicated malaria [67] and human SMA [46].…”
Section: Host Mif Seems To Be Protective In Human Malariamentioning
confidence: 99%
“…MIF is considered an integral component of the host antimicrobial alarm system and stress response that promotes the pro-inflammatory functions of immune cells [16]. MIF serum levels are significantly increased in parasitic diseases such as leishmaniasis and malaria [17][18][19], and functional polymorphism of the human MIF gene have been associated with increased susceptibility to inflammatory [20], autoimmune [21], and infectious diseases [22,23]. The MIF gene Ϫ173G/C polymorphism (rs755622) is located within the 5' promoter region, and the Ϫ173*C allele has been associated with a higher level of MIF protein [24].…”
Section: Introductionmentioning
confidence: 99%